Relative geomagnetic paleointensity of the Brunhes Chron and the Matuyama-Brunhes precursor as recorded in sediment core from Wilkes Land Basin (Antarctica) - Macrì, Patrizia; Sagnotti, Leonardo; Dinarès-Turell, Jaume; Caburlotto, Andrea (Physics of the Earth and Planetary Interiors, 2010)
International audience Paleomagnetic and rock magnetic investigation was performed on the 35-m long MD03-2595 CADO (Coring Adélie Diatom Oozes) piston core recovered on the continental rise of the Wilkes Land Basin (East Antarctica). Analysis of the Characteristic Remanent Magnetization (ChRM) inclination record indicates a normal magnetic polarity for the uppermost 34m of the sequence and a distinctive abrupt polarity change at the bottom of the core. This polarity change, which spans a 27cm thick stratigraphic interval, represents a detailed record of the Matuyama-Brunhes (M-B) transition and it is preceded by a sharp oscillation in paleomagnetic directions that may correlate to the M-B precursor event. Paleomagnetic measurements enable reconstruction of geomagnetic relative paleointensity (RPI) variations, and a high-resolution age model was established by correlating the CADO RPI curve to the available global reference RPI stack, indicating that the studied sequence reaches back to ca 800 ka with an average sedimentation rate of 4.4cm/ka. Orbital periodicities (100 ka and 41 ka) were found in the ChRM inclination record, and a significant coherence of ChRM inclination and RPI record around 100 ka suggests that long-term geomagnetic secular variation in inclination is controlled by changes in the relative strength of the geocentric axial dipole and persistent non-dipole components. Moreover, even if the relatively homogeneous rock magnetic parameters and lithofacies throughout the recovered sequence indicates a substantial stability of the East Antarctic Ice Sheet during the middle and late Pleistocene, influence of the 100 ka and 41 ka orbital periodicities has been detected in some rock magnetic parameters, indicating subtle variations in the concentration and grain-size of the magnetic minerals linked to orbital forcing of the global climate.